2021
DOI: 10.1002/cam4.4369
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening uptake and determinant factors among women in Ambo town, Western Oromia, Ethiopia: Community‐based cross‐sectional study

Abstract: Background: Cervical cancer is the second most common cancer and the leading cause of cancer-related death in Ethiopian women. About 77.6% of women died of 6294 new cases reported in 2019. Early screening for cervical cancer has substantially reduced morbidity and mortality attributed to it. In Ethiopia, most of the women visit the health facilities at the late stage of the disease in which the offered intervention is not promising. Therefore, we aimed to assess the level of cervical cancer screening uptake an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…This finding highlights the huge burden of poor CS practices among women in our region, which has been a great challenge to CCa prevention in LMIC over the years [16]. Several studies within Lagos [2,[17][18][19], other parts of Nigeria [20][21][22] and LMIC [16,[23][24][25] are consistent with the low CS rate reported in our study, and in contrast to that reported in developed countries [26,27]. This is probably due to the lack of organised screening programmes in many LMIC compared to what is obtained in developed countries resulting in opportunistic screening of few women [2,3].…”
Section: Discussionmentioning
confidence: 91%
“…This finding highlights the huge burden of poor CS practices among women in our region, which has been a great challenge to CCa prevention in LMIC over the years [16]. Several studies within Lagos [2,[17][18][19], other parts of Nigeria [20][21][22] and LMIC [16,[23][24][25] are consistent with the low CS rate reported in our study, and in contrast to that reported in developed countries [26,27]. This is probably due to the lack of organised screening programmes in many LMIC compared to what is obtained in developed countries resulting in opportunistic screening of few women [2,3].…”
Section: Discussionmentioning
confidence: 91%
“…Twenty studies informed that low knowledge about CC and its screening among women decreases the early detection of cervical cancer [ 31 50 ]. Similarly, lack of access to information on CC [ 37 ] and screening services [ 35 , 42 , 45 , 51 53 ], unawareness of where to be screened [ 54 ] and lack of health literacy [ 53 , 55 ] were the potential detractors to uptake screening. On the contrary, high knowledge of cervical cancer can improve healthcare-seeking behaviours of people at risk of CC.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, high knowledge of cervical cancer can improve healthcare-seeking behaviours of people at risk of CC. Hence, being knowledgeable on methods of prevention [ 55 66 ], availability of cervical cancer screening services [ 51 ], the consequence of advanced cervical cancer [ 51 ] and the place of cervical screening services [ 37 ] has an input on the success of cervical cancer screening programme utilization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical cancer screening techniques include visual inspection after application of acetic acid (VIA), 7 papanicolaou test (Pap), 3 , 8 and human papillomavirus (HPV) test. 9 The type of cervical cancer is confirmed by visual examination of histopathology images under a microscope.…”
Section: Introductionmentioning
confidence: 99%